Mexican Buprestidae: two new species of Acmaeodera Eschscholtz and a review of the genus Chalcophora Dejean - Westcott, Richard L.; Bellamy, Charles L. (Zootaxa, 2013)
Two distinctive new Mexican species of Acmaeodera Eschscholtz are described, A. xanthoskeles from the Yucatán Pen-insula and A. inusitata from Michoacán. The Mexican species of the genus Chalcophora Dejean, C. hondurasica Casey and C. mexicana Waterhouse, are reviewed and discussed along with two U.S. and Canadian species, C. angulicollis (Le- Conte) and C. virginiensis (Drury). Chalcophora angulicollis is shown not to occur in Texas as has long been recorded.